BLENDED LEARNING, ALTERNATIF PEMBELAJARAN ERA 4.0 - Sri Widayati; Ni’matu Sholikhah (KOLONI, 2022)
Along with development of technology, it has an impact on the learning process in schools. The learning process that used to use a traditional approach began to transform towards future learning. This learning model using blended learning is one solution in learning in the current digital era. Blended learning is a combination of learning strategies, learning methods, and online learning as well as face-to-face learning to achieve learning objectives. The application of the blended learning model must adjust the learning objectives to be achieved. Blended learning makes students more flexible in learning. Keywords: blended learning, learning strategy